Estudio a la gestión de cuentas por cobrar y liquidez de las empresas comerciales - Andrade Chávez, José Nicolas (2025)
The analysis of accounts receivable management and liquidity in commercial enterprises is essential to ensure the financial efficiency of organizations. Today, predominant factors such as the pandemic have emerged, affecting the general population and business continuity, with credits becoming a fundamental pillar for continued operation. The study was developed using a qualitative-quantitative paradigm with a descriptive orientation to establish the most important aspects of proper accounts receivable management and liquidity for the success and sustainability of commercial enterprises. This included a bibliographic investigation by searching for information from different authors and field research through the application of surveys, under the inductive-deductive and analytical-synthetic methods, allowing significant results and conclusions to be obtained about the object of study. The results determined that an adequate credit policy and proper collection methods minimize the risk of delinquency and, thus, ensure sufficient liquidity for good management. This is based on the management of cash flows and good short-term financing strategies such as contingency plans and the relationship between collection and payment terms, which promote business sustainability.